Final results of the prospective biomarker trial PETra: [11C]-MET-accumulation in postoperative PET/MRI predicts outcome after radiochemotherapy in glioblastoma - Seidlitz, Annekatrin; Beuthien-Baumann, Bettina; Löck, Steffen; Jentsch, Christina; Platzek, Ivan; Zöphel, Klaus; Linge, Annett; Kotzerke, Joerg; Petr, Jan; Hoff, Jörg van den; Steinbach, Jörg; Krex, Dietmar; et al. (Clinical cancer research, 2021)
This prospective trial investigates the association of time-to-recurrence (TTR) in glioblastoma with [11C]methionine (MET) tracer uptake before postoperative radiochemotherapy (RCT) aiming to guide radiotherapy boost regions.